2012
DOI: 10.4212/cjhp.v65i2.1116
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Dexmedetomidine Relative to Midazolam for Sedation in the Intensive Care Unit

Abstract: Background: Dexmedetomidine is an ␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
(32 reference statements)
1
29
0
2
Order By: Relevance
“…A recent Canadian economic comparison of dexmedetomidine and midazolam in critically ill adult patients concluded that although acquisition costs for dexmedetomidine are higher than those for midazolam, the decreased need for mechanical ventilation and delirium management with dexmedetomidine make this drug less costly overall. 29 Given the high frequency of withdrawal symptoms in our study and others, further research into the optimal method of dexmedetomidine discontinuation in critically ill infants and children is also warranted, as well as the long-term, particularly developmental, effects of its use in the pediatric population.…”
Section: Discussionmentioning
confidence: 79%
“…A recent Canadian economic comparison of dexmedetomidine and midazolam in critically ill adult patients concluded that although acquisition costs for dexmedetomidine are higher than those for midazolam, the decreased need for mechanical ventilation and delirium management with dexmedetomidine make this drug less costly overall. 29 Given the high frequency of withdrawal symptoms in our study and others, further research into the optimal method of dexmedetomidine discontinuation in critically ill infants and children is also warranted, as well as the long-term, particularly developmental, effects of its use in the pediatric population.…”
Section: Discussionmentioning
confidence: 79%
“…4,5 Both evaluations were based on the results of a single randomized study that compared dexmedetomidine to midazolam intravenous (IV) infusions. 6 In this randomized trial known as Safety and Efficacy of Dexmedetomidine Compared With Midazolam (SEDCOM), the median time to start of sedative agent was approximately A subsequent economic evaluation used the data from the SEDCOM trial to perform a cost minimization analysis.…”
Section: Discussionmentioning
confidence: 99%
“…). In Canada, there is an increase in healthcare cost of 23·4% (Lachaine & Beauchemin ) for clients diagnosed with delirium. The most important factor affecting the development of delirium is age (Conley ), and more Canadians are expected to experience it as they grow older.…”
Section: Introductionmentioning
confidence: 99%
“…The longterm consequences of delirium include: greater likelihood of discharge to a place other than home, greater functional decline, increased mortality rate for one year after the incidence of delirium and long-term neuro-cognitive impairment (Vasilevskis et al 2010). In Canada, there is an increase in healthcare cost of 23Á4% (Lachaine & Beauchemin 2012) for clients diagnosed with delirium. The most important factor affecting the development of delirium is age (Conley 2011), and more Canadians are expected to experience it as they grow older.…”
Section: Introductionmentioning
confidence: 99%